Subchronic Toxicity Test of Purple Leaves Ethanol Extract (PLEE) on the Histopathological Picture of the Pancreas of Wistar Rats - Yunira Wardani; Niluh Puspita Dewi; Syafika Alaydrus; Meike Rachmawati (Postgraduate, University of Mataram, 2024)
Medicinal plants are considered a rich source of bioactive metabolites and have the potential for the discovery and development of new drugs, one of which is the purple leaf plant which is known to treat various diseases. The aim of this research was to determine the effect of administering purple leaf ethanol extract over a certain period of time at doses of 500 mg/kgBB, 2.000 mg/kgBB and 5.000 mg/kgBB on the histopathology of the Wistar rat pancreas. In this study, an experimental method was used with a randomized block design, using 20 male Wistar rats which were divided into 4 research groups, 1 control group which was given Na-CMC. and 3 treatment groups were given purple leaf ethanol extract at a dose of 500 mg/kgBB (P1), dose of 2.000 mg/kgBB (P2) and dose of 5.000 mg/kgBB (P3). The test preparation was administered orally, for 28 days. The results of subchronic toxicity testing of purple leaf ethanol extract on Wistar rats carried out for 28 days, up to a dose of 5.000 mg/kg BB, showed that at a dose of 2.000 mg/kg BB – 5.000 mg/kg BB it was toxic to the histopathology of the Wistar rats pancreas, which was characterized by the presence of cell degeneration, increased organ index and the presence of symptoms of toxicity